العلاقة بين عمليات إدارة المعرفة والتدريب عن بعد في إدارة التدريب التربوي والابتعاث "بنات" بمنطقة الرياض - الدوسري، مها بنت فهد بن مبارك; السحيم، هيفاء بنت عبدالله (جامعة الإمام محمد بن سعود الإسلامية, 2022)
هدفت الدراسة إلى الكشف عن العلاقة بين عمليات إدارة المعرفة والتدريب عن بعد في إدارة التدريب التربوي والابتعاث (بنات) بمنطقة الرياض، من خلال تحديد مستوى تطبيق عمليات إدارة المعرفة (توليد المعرفة، خزن المعرفة، نشر المعرفة، تطبيق المعرفة) في إدارة التدريب التربوي والابتعاث (بنات) بمنطقة الرياض من وجهة نظر مشرفات التدريب، وتحديد مستوى التدريب عن بعد فيها، واستخدمت الدراسة المنهج الوصفي الارتباطي، والاستبانة أداة لها، وطبقت الدراسة على مشرفات التدريب وعددهن (٣٤) مشرفة، وقد استجاب منهن (٣٠) مشرفة، أي بنسبة (٨٨.٢%) من إجمالي مجتمع الدراسة. وتوصلت الدراسة إلى أن مستوى عمليات إدارة المعرفة في إدارة التدريب التربوي والابتعاث (بنات) بمنطقة الرياض جاء بدرجة (متوسطة)، كما أن مستوى التدريب عن بعد في إدارة التدريب التربوي (بنات) بمنطقة الرياض، جاء بدرجة مرتفعة، بالإضافة إلى وجود علاقة ارتباط طردية وذات دلالة إحصائية عند مستوى (٠,٠٥) فأقل بين مستوى عمليات إدارة المعرفة ككل وبأبعاده المختلفة (توليد المعرفة، خزن المعرفة، نشر المعرفة، تطبيق المعرفة) وبين مستوى التدريب عن بعد في إدارة التدريب التربوي والابتعاث (بنات) بمنطقة الرياض. The study aims to find out the relationship between knowledge management processes and distance training in the Department of Educational Training and Scholarships (Girls) in Riyadh region. By determining the application level of knowledge management processes (knowledge generation, knowledge storage, knowledge dissemination, knowledge application) in the Department of Educational Training and Scholarships (Girls) in Riyadh region from the perspective of the training supervisors, and determining the level of distance training in the department. The study applied the descriptive correlative approach. It used the questionnaire as a data collection tool. The study was applied to (n= 34) training supervisors, and (n= 30) supervisors responded, which represented (88.2%) of the total study population. The study concluded that the level of knowledge management processes in the Department of Educational Training and Scholarships (girls) in the Riyadh region came to a (medium) degree. While the level of distance training in the Department of Educational Training (girls) in the Riyadh region came to a (high) degree. It was found that there is a positive and statistically significant correlation at the level (0.05) and less between the level of knowledge management processes as a whole and its various dimensions (knowledge generation, knowledge storage, knowledge dissemination, knowledge application) and the level of distance training in the Department of Educational Training and Scholarships (girls) in Riyadh region.
Keywords: المؤسسات التربوية -- إدارة المعرفة -- التدريب التربوي -- السعودية